Expert System of Diagnosing Chikungunya Disease by Certainty Factor Method - Rahmadani Pane; Ali Akbar Ritonga; Budianto Bangun; Iwan Purnama; Sutrisno Dwi Raharjo (Jurnal Mantik, 2020)
One of the diseases distributed in the population is chikungunya fever transmitted by viruses from the genus Alphavirus, Togaviridae family, and transmitted by Aedes' bite aegypti and Ae mosquitoes. Virus albopictus involved. Chikungunya (CHIK) has three distinct symptoms: fever, joint pain (arthralgia), and skin infection (rash). Chikungunya (CHIK) is a self-limiting illness, and Chikungunya fever (CHIK) is not treated individually. Treatment efforts are symptomatic. Controlling and considering this disease is the right initiative. One consideration that can be achieved using expert system analysis is to use the form of certainty factor to derive the certainty value.